Moral distress experienced by psychiatric nurses in Japan - Ohnishi, Kayoko (Nursing ethics, 2010)
This study aimed to: (1) develop and evaluate the Moral Distress Scale for Psychiatric nurses (MDS-P); (2) use the MDS-P to examine the moral distress experienced by Japanese psychiatric nurses; and (3) explore the correlation between moral distress and burnout. A questionnaire on the intensity and frequency of moral distress items (the MDS-P: 15 items grouped into three factors), a burnout scale (Maslach Burnout Inventory — General Survey) and demographic questions were administered to 391 Japanese psychiatric nurses in 2007—2008. These nurses experienced relatively low levels of moral distress despite the fact that they were commonly confronted by morally distressing situations. All the circumstances in which the participants experienced moral distress were included in the ‘low staffing’ factor, which reflects the characteristics of Japanese psychiatric care. The frequency score of the low staffing factor was a significant predictor of burnout.